NEUTROPHIL CD64 INDEX IN SEPSIS DIAGNOSIS AFTER CARDIAC SURGERY IN INFANTS - A. A. Krivoshapkina; A. I. Subbotovskaya; O. V. Strunin; A. N. Shilova; A. A. Efimov; V. S. Kozyreva; I. A. Kornilov (Педиатрическая фармакология)
Early diagnosis of sepsis in neonates is especially relevant due to the persistently high rate neonatal mortality caused by this pathology. Active search for new laboratory markers, which would help to predict onset of a generalized infectious process with high probability, has been going on in recent years. The study was aimed at determining sensitivity and specificity of the CD64 index, evaluating the possibility of using it as an early marker of sepsis in infants after cardiac surgery during artificial circulation and comparing prognostic value of the CD64 index and the routinely used parameters. Patients and methods: the study involved 36 postoperative ICU. Retrospective analysis of bacterial inflammation markers has been conducted in groups of children at the postoperative stage: with (n = 16) and without (n = 20) sepsis. Results: the CD64 index in patients with sepsis was significantly higher than in the children without sepsis – 2.29 (p = 0.01). At the same time, blood serum C-reactive protein concentration and the absolute peripheral blood leukocyte count were similar in patients from both groups. Procalcitonin (PCT) test sensitivity for sepsis diagnosis was 65%, specificity – 67%. At the same time, the negative prognostic value of PCT reached 76%, the positive one – 63%. The performed analysis demonstrated that the CD64 index is a reliable early marker of sepsis with high sensitivity (80%) and specificity (90%); AUC – 0.895 (0.753-1.000) at cut-off point 2.00. Conclusions: C-reactive protein may not be seen as a reliable early marker of sepsis due to, it appears, peculiarities of its dynamics in the postoperative period. Specificity of this parameter is low and amounts to 50%. The study also demonstrated lower information value of the procalcitonin test compared to the CD64 index. The CD64 index over 2.00 indicates high risk of sepsis development in neonates in the postoperative period.